2016
DOI: 10.1186/s41240-016-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and activity of type IV antifreeze protein from cultured subtropical olive flounder (Paralichthys olivaceus)

Abstract: Antifreeze proteins (AFPs) lower the freezing point but not the melting point of aqueous solutions by inhibiting the growth of ice crystals via an adsorption-inhibition mechanism. However, the function of type IV AFP (AFP IV) is questionable, as its antifreeze activity is on the verge of detectable limits, its physiological concentration in adult fish blood is too low to function as a biological antifreeze, and its homologues are present even in fish from tropic oceans as well as freshwater. Therefore, we spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Gauthier et al (2008) proposed that, although type IV has the potential to develop into a functional AFP, it has not been selected for this purpose due to the presence of other functional AFPs. This is supported by the presence of type IV AFP in temperate, subtropical and tropical species, including species living in fresh water (Liu et al 2009;Xiao et al 2014;Lee et al 2011;Lee and Kim 2016). These species have no need for any freeze protection, and type IV AFP may instead be involved in embryogenesis, since several of its homologues are essential in this process.…”
Section: Type IVmentioning
confidence: 99%
See 1 more Smart Citation
“…Gauthier et al (2008) proposed that, although type IV has the potential to develop into a functional AFP, it has not been selected for this purpose due to the presence of other functional AFPs. This is supported by the presence of type IV AFP in temperate, subtropical and tropical species, including species living in fresh water (Liu et al 2009;Xiao et al 2014;Lee et al 2011;Lee and Kim 2016). These species have no need for any freeze protection, and type IV AFP may instead be involved in embryogenesis, since several of its homologues are essential in this process.…”
Section: Type IVmentioning
confidence: 99%
“…Its proposed structure consists of four amphipathic α-helixes of similar length folded in a four-helix bundle (Deng and Laursen 1998). Type IV AFP has been found in many species, including Arctic longhorn sculpin (Myoxocephalus octodecemspinosus) and shorthorn sculpin (M. scorpius) (Deng and Laursen 1998;Gauthier et al 2008) and two Antarctic nototheniids, Pleuragramma antarcticum and Notothenia coriiceps (Lee et al 2011;Lee and Kim 2016). However, its role as a functional AFP has been questioned, since it is a very weak AFP, causing only 0.07 C thermal hysteresis at a concentration of 0.5 mg/mL, and is present in blood in concentrations less than 100 μg/mL, far too low to protect these fishes against freezing in icy waters (Gauthier et al 2008;Lee and Kim 2016 AU1 ).…”
Section: Type IVmentioning
confidence: 99%
“…Based on these ndings, Gauthier et al (2008) speculated that ISP4 may not be a key antifreeze protein in the blood of polar sh when other types of antifreeze protein are present. Surprisingly, in addition to polar sh, ISP4 is also found in warm-temperate sh and freshwater sh (Nishimiya et al, 2008;Zhang et al, 2009;Kim, 2015;Lee and Kim, 2016). These reports indicate that ISP4 may have other effects as well as antifreeze activity in warm-temperate sh.…”
Section: Introductionmentioning
confidence: 99%
“…Ice structure proteins (ISPs), also known as antifreeze protein, play a role in inhibiting the growth of ice crystals, modifying ice morphology and inhibiting the recrystallization of ice via adsorption-inhibition (DeVries and Wohlschlag, 1969; Lee and Kim, 2016). ISPs lower the point of freezing non-colligatively but do not change the point of melting through adsorption on the surface of ice crystals and then inhibit ice growth, which increases the temperature gap between melting point and freezing point, and this temperature gap is termed thermal hysteresis (TH) (Barrett, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Deng and Laursen 30 showed that the concentration of the LS-12 gene in the longhorn sculpin, M. octodecimspinosis , is so low that without concentration of the protein, antifreeze activity could not be detected. A protein homologlous to the M. octodecimspinosis LS-12/TypeIV AFP from the subtropical olive flounder ( Paralichthys olivaceus ), 31 which does not require AFPs for survival, has been cloned, heterologously expressed (in E. coli ) and assayed for antifreeze activity. Based on its comparatively “very weak” thermal hysteresis activity (0.07 ± 0.01°C at 0.5 mg/mL), the P. olivaceus LS-12 homolog would not prevent freezing at subzero temperatures.…”
Section: Introductionmentioning
confidence: 99%